2012
DOI: 10.1111/j.1751-0813.2011.00870.x
|View full text |Cite
|
Sign up to set email alerts
|

DisseminatedScedosporium prolificansinfection in a German Shepherd dog

Abstract: Disseminated Scedosporium prolificans infection in a 1-year-old female spayed German Shepherd dog is described. Clinical signs were predominantly associated with fungal pyelonephritis and the organism was cultured from the urine. The dog was treated with itraconazole and later, terbinafine was added. Subsequent antifungal susceptibility testing of the isolate showed it to be resistant to all available antifungal drugs. The dog was euthanased because of acute abdominal haemorrhage and associated clinical deteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…prolificans, 14 Scopulariopsis chartarum, 52 Aspergillus terreus, 34 Cryptococcus neoformans, 8 Candida albicans, 5 Ochroconis gallopavum, 46 Xylohypha bantiana, 43 and Acremonium spp. 45 The protozoa identified in dogs with splenitis include Neospora caninum, 18 Hepatozoon canis, 3,16 Trypanosoma cruzi, 29 and Leishmania chagasi.…”
mentioning
confidence: 99%
“…prolificans, 14 Scopulariopsis chartarum, 52 Aspergillus terreus, 34 Cryptococcus neoformans, 8 Candida albicans, 5 Ochroconis gallopavum, 46 Xylohypha bantiana, 43 and Acremonium spp. 45 The protozoa identified in dogs with splenitis include Neospora caninum, 18 Hepatozoon canis, 3,16 Trypanosoma cruzi, 29 and Leishmania chagasi.…”
mentioning
confidence: 99%
“…In contrast to S. apiospermum , which is commonly found in soil, sewage and polluted waterways, S. prolificans is more commonly isolated from soil and potted plants and has a more restricted geographical distribution with the majority of cases in humans reported in Australia and Spain [2] . Interestingly, one of the two previously reported cases of disseminated S. prolificans infection in dogs also occurred in Australia [7] , with the other occurring in New York [9] . Scedosporiosis in humans represents a broad spectrum of clinical disease including local cutaneous and subcutaneous infection (eumycetoma) that occur secondary to penetration wounds; saprobic involvement of a previously damaged bronchopulmonary tree; invasive pulmonary disease; sinopulmonary and central nervous system infection associated with near drowning׳s in polluted water ways contaminated with P. boydii ; and disseminated infection.…”
Section: Discussionmentioning
confidence: 94%
“…This is the first report of disseminated mycosis due to S. prolificans in a Labrador retriever dog. Previous reports of disseminated scedosporiosis in dogs have been restricted to German Shepherd dogs (GSD) [5–9] , and were due to S. apiospermum infection [5,6,8] except in one case of S. prolificans infection [7] . There is a single case reported of disseminated S. prolificans (previously S. inflatum ) infection in another breed; a Beagle with osteomyelitis and pulmonary involvement [9] .…”
Section: Discussionmentioning
confidence: 99%
“…Scedosporium prolificans is an opportunistic fungal pathogen. This case report describes a young female German Shepherd dog that was presented with 3‐week history of polyuria, polydipsia, lethargy, reduced appetite, weight loss and urinary incontinence 6 . She developed a right‐sided head tilt and horizontal nystagmus, which the authors suggested was caused by metronidazole therapy.…”
Section: Small Animalsmentioning
confidence: 98%